Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Spatial confinement in zeolites dominates pentene monomolecular cracking pathway - Fang Li; Weiyong Zhong; Min Sun; Yiran Wang; Penghe Zhang; Yueming Liu; Mingyuan He (Chemical Engineering Journal, 2026)

Suppressing spectral broadening via intramolecular noncovalent interactions for high-efficiency solution-processed multi-resonance TADF OLEDs - Tao Zhou; Guimin Zhao; Yumiao He; Taiping Chen; Wenwen Tian; Yueming Sun; Wei Jiang (Chemical Engineering Journal, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Organic matter supply triggers rapid microbial-driven changes in carbon-nitrogen cycling in subterranean estuary sediments - Danqing Sun; Longyun Lai; Yueming Wu; Ying Wu; Jian Li; J. Severino P. Ibánhez; Shan Jiang (Marine Chemistry, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

An on-tissue parallel d0/d20-meladrazine derivatization approach for fatty acid peroxidation products imaging in adult zebrafish - Ji Yang; Yue Sun; Yueming Li; Zhonghua Wang; Zeper Abliz; Zhi Zhou (Analytica Chimica Acta, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Non-linear interaction behavior of mixed industrial solid wastes in circulating fluidized beds: Reacting MP-PIC simulation - Minmin Zhou; Xiuzhi Wang; WenQiang Chen; Qiuchen Sun; DongFu Wang; Zhijiang Han; Chenxi Lu; Yueming Wang; Lunbo Duan; Wojciech P. Adamczyk (Fuel, 2026)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Bioinspired graphene-based aerogel polyurethane multifunctional coatings with high-temperature resistance, anti-corrosion and anti-fouling properties - Yuping Liu; Limei Tian; Jie Zhao; Jiarun Tian; Yueming Wang; Jiyu Sun (Chemical Engineering Journal, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Water Body Characterization and Classification in Coal Mining Subsidence Areas: Insights from the Huainan Coalfield - Yueming Sun; Yanling Zhao; Zhibin Li; Yanjie Tang (Natural Resources Research, 2025)

Passive Synthetic Aperture for Direction-of-Arrival Estimation Using an Underwater Glider with a Single Hydrophone - Yueming Ma; Jie Sun; Shuo Li; Tianze Hu; Shilong Li; Yuexing Zhang (Journal of Marine Science and Engineering, 2025)
This paper addresses the aperture limitation problem faced by array-equipped underwater gliders (UGs) in direction-of-arrival (DOA) estimation. A passive synthetic aperture (PSA) method for DOA estimation using a single hydrophone mounted on a UG is proposed. This method uses the motion of the UG to synthesize a linear array whose elements are positioned to acquire the target signal, thereby increasing the array aperture. The dead-reckoning method is used to determine the underwater trajectory of the UG, and the UG’s trajectory was corrected by the UG motion parameters, from which the array shape was adjusted accordingly and the position of the array elements was corrected. Additionally, array distortion caused by movement offsets due to ocean currents underwent linearization, reducing computational complexity. To validate the proposed method, a sea trial was conducted in the South China Sea using the Haiyi 1000 UG equipped with a hydrophone, and its effectiveness was demonstrated through the processing of the collected data. The performance of DOA estimation prior to and following UG trajectory correction was compared to evaluate the impact of ocean currents on target DOA estimation accuracy.

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Stability analysis on the positioning of steel caisson foundations during submerging stage under complex marine conditions - Minglin Chen; Yong Xiao; Yueming Jin; Yonggan Sun; Bo Huang (Ocean Engineering, 2025)

Higher dynamic and turnover yet enhanced organic carbon burial in Spartina alterniflora sediments: A case study in a temperate coastal wetland - Yueming Wu; Beiyun Xu; Danqing Sun; Shan Jiang; Jian Li; Yiyun Wang; Ying Wu (CATENA, 2025)

Development of an integrated online deposition and corrosion monitoring system in a full-scale solid waste CFB boiler - Yueming Wang; Jinghui He; Yuxing Wang; Feiyue Sun; Chenxi Lu; Shuo Zhang; Lunbo Duan (Waste Management, 2024)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Free and Forced Vibration Characteristics of a Composite Stiffened Plate Based on Energy Method - Xin Gu; Xianzhong Wang; Weiguo Wu; Jie Sun; Yongshui Lin; Yueming Fang (Journal of Marine Science and Engineering, 2024)
The composite stiffened plate has garnered significant attention in the lightweight design of ship structures due to its superior mechanical properties. Although it reduces the structural weight, it also increases vibration sensitivity. Thus, investigating the vibration characteristics of the composite stiffened plate is crucial. This paper proposed a theoretical model based on the energy principle and the improved Fourier series method (IFSM) to analyze the composite stiffened plate vibration characteristics. The model demonstrates high reliability and accuracy, as confirmed through convergence analysis and comparison with experimental results from the published literature. Results indicate that geometry and material parameters significantly impact the natural frequency and can mitigate vibration responses by increasing thickness and stiffness. Additionally, ply design parameters markedly influence the vibration of composite stiffened plates, enhancing low-frequency vibration performance through optimal ply design. The structural parameters of the stiffeners, particularly the height and number of stiffeners, play a crucial role, enhancing stiffness and reducing the vibration responses of the composite stiffened plates.

Mn2+ recycling in hypersaline wastewater: unnoticed intracellular biomineralization and pre-cultivation of immobilized bacteria - Huaxiao Yan; Shengping Jin; Xiaolei Sun; Zuozhen Han; Hongmei Wang; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; Lirong Wei; et al. (World Journal of Microbiology and Biotechnology, 2024)

Water quality and microecosystem of water tanks in karst mountainous area, Southwest China - Qigang Wang; Guanghui Jiang; Ziyong Sun; Yueming Liang; Fan Liu; Jie Shi (Environmental Science and Pollution Research, 2024)

Transmedia Performance Research and Motion Control of Unmanned Aerial–Aquatic Vehicles - Xiangren Sun; Jian Cao; Yueming Li; Haipeng Li; Weikai Wang (Journal of Marine Science and Engineering, 2023)
This paper presents an improved motion controller based on the backstepping method to address nonlinear control challenges in unmanned aerial–aquatic vehicles (UAAVs), enabling them to navigate between two different media. The nonlinear control approach is applied to UAAV motion control, incorporating filters to improve stability. The study designs motion controllers for three UAAV phases: underwater, in the air, and transitioning between media. Fluid simulations of the emergence process of the UAAV for future field experiments were conducted. By fine-tuning the simulations, a comprehensive understanding of the vehicle’s performance is obtained, offering crucial insights for the development of subsequent control systems. Simulation results confirm the controller’s ability to achieve target trajectory tracking with control system responses that meet practical requirements. The controller’s performance in attitude control and trajectory tracking is verified in underwater gliding, transmedia transitions, and airborne phases, demonstrating its effectiveness.

Coupling strength between omnivory loops and their one-species-delete subloops drives real food web stability - Jianfeng Feng; Shengpeng Li; Xiaoxiao Li; Yueming Jiang; Ruyue Wang; Xianhao Meng; Wei Yang; Tao Sun; Peter C. de Ruiter; Yongtang Shi; Nils Chr. Stenseth (Theoretical Ecology, 2023)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Research on the hydrodynamic performance of AUVs in small size open channel area - Jian Cao; Yaoqi Feng; Yueming Li; Hongwei Li; Chao Han; Yushan Sun; Zhaohang Liu (Ocean Engineering, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Effect of aluminate content in cement on the long-term sulfate resistance of cement stabilized sand - Kaiwei Liu; Yueming Wang; Ning-Jun Jiang; Aiguo Wang; Daosheng Sun; Xingxing Chen (Marine Georesources & Geotechnology, 2020)

Experimental Research on the In Vitro Antitumor Effects of Crataegus sanguinea - Jianling Sun; Guolan Gao; YuLian Gao; liJuan Xiong; Xiaoying Li; Jihong Guo; Yueming Zhang (Cell Biochemistry and Biophysics, 2013)

Retinol-binding protein 4 as a risk factor for cholesterol gallstone formation - Tao Han; Diancai Zhang; Zan Fu; Yueming Sun; Wei Yang; Cuimei Yuan (Molecular and Cellular Biochemistry, 2013)

Overexpression of d-psicose 3-epimerase from Ruminococcus sp. in Escherichia coli and its potential application in d-psicose production - Yueming Zhu; Yan Men; Wei Bai; Xiaobo Li; Lili Zhang; Yuanxia Sun; Yanhe Ma (Biotechnology Letters, 2012)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

Post-stack reverse-time migration using a finite difference method based on triangular grids - Shujuan Guo; Zhenchun Li; Xiaodong Sun; Yueming Ye; Houhua Teng; Fang Li (Applied Geophysics, 2008)